Conflictos familiares y su influencia en la depresión en una mujer de 37 años en la Unidad Educativa Padre Marcos Benetazzo - López Barbotó, Ivonne Gardenia (2021)
In this case study, the topic Family conflict and its influence on depression in a 37-year-old woman in the “Padre Marcos Benetazzo” Educational Unit, a resident of the Babahoyo canton, Los Ríos province, was discussed. collect the necessary data for its preparation, through interviews and a psychological instrument such as the Beck Depression Inventory, which was carried out on the patient, whose result was mild depressive disorder. It should be noted that family conflicts often cause certain disorders, as is the case of depression that involves a series of negative conceptions of oneself, the world and the future. For which, a cognitive-behavioral psychotherapeutic scheme was carried out in the patient to regain her emotional stability, enjoy good self-esteem and mental health in general.